A falha muscular não é necessária para maximizar as adaptações neuromusculares ao treinamento de força - Nóbrega, Sanmy Rocha (2016)
Resistance training (RT) is the main method to promote increases in muscle strength and hypertrophy, in which loads higher than 60% of one repetition maximum (1-RM) are commonly recommended. Other studies suggest performing RT to the point of muscle failure, which can be defined as the inability to move a load beyond a critical angle or as the inability to complete a repetition in a full range of motion due to fatigue, in order to maximize strength gains and hypertrophy. However, it is still unclear if RT to muscle failure is really necessary. Thus, the aim of this study was to discuss the effects of RT to failure on motor units (MUs) recruitment and adaptive responses, providing arguments to how RT to failure might differently affect muscle adaptations on different populations. In conclusion, evidence regarding untrained individuals suggests that high-intensity RT (HIRT) to failure is not necessary for maximal increases in strength and mass. On the other hand, performing RT to failure might be necessary for optimal increases in strength and mass when training at low intensities (LIRT). Regarding trained individuals, evidence point greater strength gains when HIRT is performed to failure. Nonetheless, muscle failure seems to be an interesting strategy when it comes to optimizing hypertrophy gains for trained individuals.